La rivoluzione cubana in Colombia (1958-1974) (2022)
The Cuban Revolution was a global, generational and deeply political revolution; it penetrated the customs of society, the lifestyles, the way of dressing, writing, singing and traveling. Within the multipolar and frenetic context of the Cold War, his case took on an unexpected and disruptive dimension and extension: only a few countries were immune from its message and its activities. His strength was overwhelming. The space of Latin America and the arena of the left were the two fields in which it most materialized as an element of fracture. In this context, this thesis has deepened the dynamics connected to the circulation of the Cuban example within Colombia, which turns out to be an emblematic case study, although it has influenced its state structure, its society, its wide field of the political left and subversive movements within it. From the historiographical point of view, this work represents a contribution, within the research field of political history, institutions and conflicts, to the understanding of the dynamics that oscillate between political practices that have resulted in strong contests for power and at the same time, the way in which imaginaries are constructed in constant tension around concrete political phenomena, as in this case, the Cuban Revolution. In particular, the first and second part of the thesis are dedicated to the historical-political dynamics of Colombia, the international left and the Colombian left. Colombia, still upset by the traumas of the so-called period of the Violencia and returning from the conclusion of the military experience of General Gustavo Rojas Pinilla, was led towards an institutional pacification by its main parties, the Liberal Party and the Conservative Party, which took the name of Frente Nacional. The simultaneous victory of the revolutionaries in Cuba was a further trauma for the country and entire social categories, from students to workers, from the middle classes to political parties, from priests to peasants, during the 1960s, were absorbed by this vortex which also raged across the continent. The historiographical problem of the research, deepened in the third and fourth part of the thesis in the relationship between cultural history and political history, therefore concerns the ways in which the "fracture" represented by the Cuban Revolution permeated in various ways the entire life of Colombia in the circulation of ideas, in the practices, in the narratives and in the construction of imaginaries that were a field of dispute for various social actors and in the ideological and material formation of party, social and guerrilla movements. The Cuban imagery that was built was the result of targeted work by the island government, which made its message convey through the numerous mass media of the time: magazines, newspapers, documentaries, films, books, radio. Colombian cultural actors took up this narrative and made themselves the vectors of this dynamic through the cultural tools at their disposal. The thesis of this work argues that in Colombia, in the period between 1958 and 1974, a complex narrative was constructed around the Cuban Revolution, which reached mass dimensions. The elements that make up this narrative served to legitimize the cause of those who wanted to follow "the Cuban example" and those who wanted to oppose it. The magazines and periodicals analyzed in the text, (Mito, Documentos Políticos, Voz de la Democracia and El Tiempo), played a role of conscious agents in the dissemination of the successes and defeats, of the proposals and errors, of the achievements and difficulties of the government led by Fidel Castro. These publications therefore created a public opinion, educated and manipulated it, actively participating in the internal circulation of its narrative and in the collective mobilization it generated.